Sexism In Okky Madasari's The Years Ofthe Voiceless - Tirafiah, Octria, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
This study is aimed to show how sexism is depicted in The Years of the Voiceless novel by using feminist approach. It is done by determining two objectives: the first is analyzing the novel based on feminist analysis and the second is analyzing the novel based on the issue raised by the writer.This research is descriptive qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is The Years of the Voiceless novel written by Okky Madasari released in 2013. Whereas the secondary data sources are other materials taken from books or e-books, journals, internet related to the study. They are collected through library study and analyzed by descriptive analysis.The study draws the following conclusions. Firstly, based on the feminist analysis of The Years of the Voiceless novel written by Okky Madasari conveys the message through the major character. The major character of this novel is Marni. Marni struggles to be able to take part in domestic activity and a wider range makes her fall up to face men and rulers. In The Years of the Voiceless novel, equality between women and men is still sorely lacking. It can be viewed in terms of economic, political, security, and social activities especially for Marni. Secondly, the analysis divides into two based on sexism types; hostile sexism and benevolent sexism. Hostile sexism regards as an attitude inferior towards women as reflected in the novel. Research findings on this section are divided into three terms: taking control in arguing participation, inappropriate in wielding over economic, and lack of regard in women's dignity and self-esteem. While in benevolent sexism the writer classifies it into two, justifying women in chivalrous attitude and complementary of men's lack. Both hostile sexism and benevolent sexism are different. Hostile sexism shows an attitudes in dominating society by men. Benevolent sexism involves subjectively favorable, chivalrous attitudes towards women whom need an affection and support.